2008
DOI: 10.1002/jmv.21359
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the BC‐loop of the BKV VP1 region do not influence viral load in renal transplant patients

Abstract: The reactivation and replication of the BK polyomavirus (BKV) leading to BKV-associated nephropathy (BKVAN) is one of the major complications in renal transplantation patients. BKV isolates were classified into four subtypes (I-IV) based on genotype variations within the VP1-coding region. The type-specific amino acid differences cluster within the BC-loop of the major capsid protein VP1. As demonstrated in vitro, mutations in this region also play a role in the infectivity, attachment and stability of viral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 34 publications
(44 reference statements)
4
19
0
Order By: Relevance
“…In a recent study, mutations in the BC-loop of BKV isolates obtained from urine samples of 45 kidney transplant patients were determined (Krautkramer et al, 2009). Two of the mutations (E82D and H139N) reported by these authors were also identified in this study in RTR17 and RTR26, in a BKV isolate in the CSF of one neurological patient (NP4) and in two out of six of our bone marrow transplant patients (BMT31 and BMT32).…”
Section: Vp1 Polymorphism and Cell Tropismmentioning
confidence: 77%
See 2 more Smart Citations
“…In a recent study, mutations in the BC-loop of BKV isolates obtained from urine samples of 45 kidney transplant patients were determined (Krautkramer et al, 2009). Two of the mutations (E82D and H139N) reported by these authors were also identified in this study in RTR17 and RTR26, in a BKV isolate in the CSF of one neurological patient (NP4) and in two out of six of our bone marrow transplant patients (BMT31 and BMT32).…”
Section: Vp1 Polymorphism and Cell Tropismmentioning
confidence: 77%
“…This is exemplified by BKV variants 1, 4, and 11 which were present in several patient groups. A lack of such correlation has earlier been reported in nephropathy and SLE patients (Jin et al, 1995;Bendiksen et al, 2000a;Baksh et al, 2001;Randhawa et al, 2002;Boldorini et al, 2009;Krautkramer et al, 2009;Tremolada et al, 2010a,b). Identical strains (variants 1, 4, and 11) were detected in different patient groups, suggesting that a particular BKV strain is not associated with a specific disease.…”
Section: Vp1 Polymorphism and Cell Tropismmentioning
confidence: 82%
See 1 more Smart Citation
“…In one study, single base-pair mutations were detected more frequently in samples from patients with BK nephropathy, but amino acid changes were randomly distributed in BK nephropathy patients and controls (28). Other studies have identified amino acid changes in the external loops of VP1, which mediate BKV attachment to target cells but did not find an association with viral load or incidence of BK nephropathy (29,30). Similarly, amplifications, deletions, and rearrangements in the NCCR have not been shown to influence the development of hemorrhagic cystitis or BK nephropathy in either HCT or kidney transplant recipients (27,31).…”
Section: Discussionmentioning
confidence: 99%
“…It is this genomic diversity that is responsible for discrepancies in the research on the clinical relevance of BKV and its associations with BKVN. For example, whereas Krautkramer et al [2009] found no correlation between mutations in BKV VP1 genes and BKV viral load, Boldorini et al [2009b] identified a correlation between BKVN and the frequency of single base-pair mutations in BKV DNA. On the other hand, Chan et al [2009] described observing a case of BKVN in which a BKV large-T antigen was unreactive.…”
Section: Introductionmentioning
confidence: 89%